Milk, Yogurt and Butter in Medieval East Asia: Dairy Products from China to Japan in Medicine and Buddhism - Kotyk, Jeffrey (Religions, 2021)
Dairy products have existed in China from at least the Han Dynasty onward. Later, under the influence of Buddhism, dairy items such as yogurt, butter and ghee were required for ritual purposes. The domestic dairy industry in medieval China is an understudied topic, but even more so is the use of dairy in contemporary Japan, where Chinese traditions of Buddhism were transplanted in full. The kanji describing various dairy products were also known in Japan, but we must ask whether these substances were available in Japan, and to what extent. Unlike luxury consumables such as aromatics and medicines, perishable foodstuffs were unlikely to have been transported from the mainland. This study will document and discuss the transmission of a dairy industry from China to Japan, with a focus on the role of these products in religious and medical contexts.